Optimal order yielding discrepancy principle for simplified regularization in Hilbert scales: finite-dimensional realizations - Santhosh George; M. Thamban Nair (International Journal of Mathematics and Mathematical Sciences)
Simplified regularization using finite-dimensional approximations in the setting of Hilbert scales has been considered for obtaining stable approximate solutions to ill-posed operator equations. The derived error estimates using an a priori and a posteriori choice of parameters in relation to the noise level are shown to be of optimal order with respect to certain natural assumptions on the ill posedness of the equation. The results are shown to be applicable to a wide class of spline approximations in the setting of Sobolev scales.